2017
DOI: 10.18632/oncotarget.22506
|View full text |Cite
|
Sign up to set email alerts
|

Effect modification by region in the associations ofLEP G2548AandLEPR Q223Rpolymorphisms with statin-induced CK elevation

Abstract: We investigated the associations of LEP G2548A and LEPR Q223R polymorphisms with statin-induced creatine kinase (CK) elevation among Chinese patients with hyperlipidemia. A total of587 enrolled individuals were treated with 20 mg/d oral simvastatin for 8 consecutive weeks. Genotyping of LEP G2548A and LEPR Q223R were conducted using PCR-RFLP. Multiple regression analyses showed that, in the Dongzhi region only, patients carrying the LEP AA genotype had a significantly greater increase in CK levels compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
2
0
2
Order By: Relevance
“…Five papers investigated associations between various genetic variants with statin-induced ADRs, studying the effects of either just one statin [ 33 , 77 ] or multiple statins [ 78 , 79 , 80 ] ( Table 2 ). As the studies used different methods in determining statin-induced ADRs and studied different genes, direct comparisons to derive a definitive conclusion were not possible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five papers investigated associations between various genetic variants with statin-induced ADRs, studying the effects of either just one statin [ 33 , 77 ] or multiple statins [ 78 , 79 , 80 ] ( Table 2 ). As the studies used different methods in determining statin-induced ADRs and studied different genes, direct comparisons to derive a definitive conclusion were not possible.…”
Section: Resultsmentioning
confidence: 99%
“…The study with the largest cohort classified statin-induced myopathy based on CK levels and geographic location in China (392 patients from Dongzhi and 195 patients from Beijing) over two time points, specifically after 4 weeks’ and 8 weeks’ treatment with simvastatin [ 77 ]. Jiang et al [ 77 ] only found significant elevation of CK levels among patients in Dongzhi with either the AA genotype in the LEP G2548A variant and RR or QQ genotypes of the LEPR Q233R variant. However, this finding was not replicated in patients from Beijing.…”
Section: Resultsmentioning
confidence: 99%
“…Como ya se ha mencionado, la relevancia del trasfondo genético en el desarrollo de la obesidad y sus comorbilidades es demostrada, pero las asociaciones aun no son definitivas (Garcés et al, 2016). La frecuencia del alelo G en los SNP de LEP, se ha encontrado "significativamente mayor" en personas con sobrepeso y obesidad, cuando se ha asociado con niveles de leptina, IMC, masa grasa y presión arterial (Jiang et al, 2017). Cabe mencionar que otros estudios no han logrado demostrar alguna asociación consistente entre los polimorfismos de LEP o LEPR y obesidad (Garavito et al, 2020).…”
Section: Resumen Narrativo De Los Resultados De Los Estudios Revisado...unclassified
“…Los polimorfismos LEP G-2548A y LEPR Q223R han sido variables asociadas a diferentes comorbilidades en diferentes poblaciones (Jiang et al, 2017). Meshkani y colaboradores (2016) investigaron la asociación de estas variantes génicas con diabetes tipo 2, en población iraní de ambos sexos.…”
Section: Resumen Narrativo De Los Resultados De Los Estudios Revisado...unclassified